The Use of Artificial Intelligence in Digital Era Learning for Islamic Education Teachers Facing Generation Z - Saiddaeni Saiddaeni (Universitas Sebelas Maret, 2024)
Abstract: Start The purpose of this article is to provide Islamic religious education teachers with further options for technological developments by utilizing AI in learning. As well as how teachers can utilize AI to help the teaching and learning process in the classroom. Technology and progress in the digital age are unavoidable and the knowledge gap between generation Z and previous generations regarding technology and information. This article uses a descriptive qualitative method with a netnography approach. Primary sources from websites, scientific journals, literature, online media news related to the research. The data collection method is done by reading, analyzing, and recording various literature materials. The results obtained that, learning Islamic religious education can be integrated with technology effectively. As other sciences can use by integrating AI technology. Classical methods that only use lectures as a technique for delivering learning materials have shortcomings in terms of utilizing technology in today's digital era. Teachers in today's digital era are required to be fluent in using technology. For this reason, the use of AI is important to integrate and adjust to the current generation Z who live in the digital age.